Avaliação do processo de dispensação de imunossupressores para transplantados renais, SES MG, 2008 - Daniel Emilio da Silva Almeida (2012)
Introduction: The phenomenon of population ageing observed in Brazil tends to increase the demand for chronic diseases health services. Currently, it is estimated that more than two million Brazilians have some degree of renal dysfunction, a fact that has been aggravated by the progressive increase in the number of individuals with kidney disease in Brazil. During its late stage, known as End Stage Renal Disease (ESRD), the kidney loses its function progressive and irreversibly. The incidence and prevalence of chronic kidney diseases imply maintaining a high number of patients on renal replacement therapy, which includes transplantation, but also necessary medication and post-transplant follow-up as its modalities, everything provided by the Unified Health System (SUS). This situation has generated a high cost to the public health system in Brazil. The Clinical Protocols and Therapeutic Guidelines (PCDT) approved by the Ministry of Health recommend maintaining the state of immunosuppression in renal transplantation with the use of drug regimens, where the main drug used is cyclosporine. In Minas Gerais, mycophenolate sodium is the immunosuppressive more dispensed by the Secretary of State for Health (SES / MG) for kidney transplant patients. In this context, studies aiming to evaluate the efficacy and safety of treatment options and their usage profile may be useful for planning and organizing health services, in order to promote rationality in their actions and to avoid the danger related to health and the exacerbated financial costs due to the growing multiplicity of new technologies in health. Objective: Evaluating the process of dispensing immunosuppressive drugs for maintenance of kidney transplants in the state of Minas Gerais. Methods: The study has two components. The first, a systematic review with meta-analysis, aiming to identify, summarize and evaluate, by comparison, efficacy and safety data of immunosuppressive drugs azathioprine and mycophenolate mofetil or sodium (enteric), used in immunosuppressive therapy in patients who underwent renal transplantation. We performed a search for articles through July 2011 in MEDLINE, Pubmed interface, Latin American Literature in Health Sciences - LILACS, Cochrane Renal Group and Records Center Cochrane controlled trials. We selected randomized controlled trials and quasi-randomized trials, with follow-up to more than six months and comparing pharmacological regimes including the immunosuppressant azathioprine, mycophenolate mofetil or enteric with any combination and dose maintenance therapy. To assess the methodological quality of clinical trials were used the Jadad scale modified and the Cochrane Collaboration tool. Statistical analysis was performed by the software RevMan 5.0 from the Cochrane Collaboration. The dichotomous results were expressed as risk ratio (RR) and their differences were analyzed using chi-square test and I2. The second component comprises a study of drug usage, transversal, which aimed to evaluate the process of dispensing immunosuppressants by SES / MG. The study population consisted of all kidney transplant recipients who requested immunosuppressants to the Program for High Cost Drugs in 2008. Related variables were selected: i. demographic profile (age and sex), ii. characteristics of the application process (Regional Health Management source, proceeding of the necessary steps to grant the request and current status - approved, rejected or under evaluation), iii. drug dispensed (presentations, monthly cost and prioritization in PCDT). The analysis of the application process considered seven steps to the final approval of immunosuppressive drugs. To analyze the suitability of the required immunosuppressive 19 regimes, it was considered, in PCDT, the general guidelines of medicine prioritization according to the main types of transplants, obeying a rational sequence of continuity in relation to initial immunosuppressive therapy. Descriptive analyses were performed using proportions, measures of central tendency and dispersion. In the statistical analysis, the chisquare test to compare proportions and Student t test and Mann-Whitney test were employed to compare means. The level of significance was considered at 5%. The software used was SPSS ® version 17.0. Results: In the systematic review, ten studies comparing AZA versus MMF in the qualitative analysis were selected and included. Of these, eight were included in the meta-analysis. It was observed in scientific literature better results for acute rejection in the groups using MMF, results endorsed by a meta-analysis of 12 months. However, there were not statistically significant and favorable results for graft and patient survival, which are most important variables for determining the patients therapy. Considering the results for safety, most of the articles showed a higher number of adverse events for the groups that made use of mycophenolate mofetil for the follow-up of six, twelve or thirty-six months. Regarding the cross-sectional study, in 2008, 964 cases were opened with the code Z94.0 related to kidney transplant (ICD-10), and 915 (94.9%) of those requested at least one immunosuppressive agent. We identified 687 patients responsible for these processes, predominantly male (n = 423, 61.6%), mean age 42.9 ± 14.1 years (median 46, range 2-79 years). The great majority of drugs (87.4%, n = 1288) were classified as 2nd choice (mycophenolate sodium, tacrolimus and sirolimus), with only 12.6% (185) of first choice (cyclosporine and azathioprine), which represents an increase of at least 301% in the cost of treatment compared to first choice therapy. We can note that in the analyzed period, the processing of the requests took an average of about 22 days to complete, giving a faster proceeding in the second half of the year. Comparing the profile of cases of patients who requested first-choice and mixed therapy drugs to those who requested second choice schemes, the GRS-BH had a lower proportion of dispensing drugs of first choice in relation to all other GRS's (p <0.05). Assessing the profile of drug dispensing process by origin of the request, it still could be seen statistically significant differences in the average processing time of cases, with greater agility in the GRS-BH. Conclusion: The efficacy and safety profile from scientific evidence currently available strongly suggests that the immunosuppressive drug therapy should take into account other aspects than the medicine, such as patient, donor and population characteristics (risk for immunological and non-immune factors), since there is no scientific proof of the superiority of one medicine over the other, regardless all clinical situation considered. Moreover, the study showed a proportion of dispensing drugs which widely favors the second-line drugs. Such behavior is not only contrary to the PCDT, but also it is not adequately supported by scientific evidence regarding the efficacy of these immunosuppressive drugs. Scientific productions raise serious discussions about the use of second-line drugs so extensively. Greater caution is required, as well as continuously incorporation of high-level evidence to PCDT and regular studies about the profile of dispensing drugs and their users, in order to improve quality and rationality in health care. The results from this study indicate the importance of using methods of evaluation of health technologies, as well as epidemiological studies, in order to optimize the performance of health services, according to the principles of the SUS.